2008
DOI: 10.1007/s11064-008-9790-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Caffeine on l-Arginine Metabolism in the Brain of Rats

Abstract: In our study, the short-term effects of caffeine on L-arginine metabolism in the brains of rats were investigated. Caffeine was given orally at two different doses: 30 mg/kg and 100 mg/kg (a high non-toxic dose). Brain tissue arginase activity in rats from the caffeine-treated groups decreased significantly compared with the control group. Malondialdehyde (MDA) levels in the brain tissue and serum of animals in the caffeine groups also decreased significantly. Brain tissue and serum nitric oxide (NO) levels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Also caffeine's ability to mop up peroxide radicals [63] may be responsible for the slight increase in SOD activity seen at low doses of caffeine in this study. However, studies have also shown that the effects of caffeine on antioxidant status are dose related; with reports of increased oxidative stress with high doses of caffeine [67], [68]. The significant increase in SOD activity and decrease in GPX activity seen in this study (with increasing doses of caffeine) is suggestive of oxidative stress.…”
Section: Discussionsupporting
confidence: 65%
“…Also caffeine's ability to mop up peroxide radicals [63] may be responsible for the slight increase in SOD activity seen at low doses of caffeine in this study. However, studies have also shown that the effects of caffeine on antioxidant status are dose related; with reports of increased oxidative stress with high doses of caffeine [67], [68]. The significant increase in SOD activity and decrease in GPX activity seen in this study (with increasing doses of caffeine) is suggestive of oxidative stress.…”
Section: Discussionsupporting
confidence: 65%
“…These results suggest that acknowledged mechanisms of the action of caffeine, like increased NO production (Ofluoglu et al 2009;Corsetti et al 2008) or its antioxidant activity (Scharf et al 2001)) are not involved in the reversal of age-related insulin resistance induced by the drug.…”
Section: Discussionmentioning
confidence: 88%
“…between 10:00 a.m. and 10:30 a.m. This caffeine dose is known as high but nontoxic (Deurveilher et al 2006;Lage et al 2006;Pettenuzzo et al 2008;Ofluoglu et al 2009;Westerterp-Plantenga 2010). After being injected, the rats were returned to their home cage and given food and water ad libitum.…”
Section: Caffeine Administrationmentioning
confidence: 99%
“…During 7 days, caffeine was given in drinking water (0.5 g/L and 1.0 g/L). The control group was given distilled water (Méndez et al 2008;Ofluoglu et al 2009), and both body weight and food intake were monitored every day. Caffeine consumption, at both doses, significantly reduced body weight over the course of the 7 days ( Figure 1A).…”
Section: Effects Of Caffeine On Body Weight and Food Intakementioning
confidence: 99%
See 1 more Smart Citation